Nutritional Risk, Health Outcomes, and Hospital Costs Among Chinese Immobile Older Inpatients: A National Study - Liu, Hongpeng; Song, Baoyun; Jin, Jingfen; Liu, Yilan; Wen, Xianxiu; Cheng, Shouzhen; Nicholas, Stephen; Maitland, Elizabeth; Wu, Xinjuan; Zhu, Dawei; Chen, Wei (Frontiers in Nutrition, 2021)
Purpose: Evidence of the impact of nutritional risk on health outcomes and hospital costs among Chinese older inpatients is limited. Relatively few studies have investigated the association between clinical and cost outcomes and nutritional risk in immobile older inpatients, particularly those with neoplasms, injury, digestive, cardiac and respiratory conditions. Methods:This China-wide prospective observational cohort study comprised 5,386 immobile older inpatients hospitalized at 25 hospitals.All patients were screened for nutritional risk using the Nutrition Risk Screening (NRS 2002).A descriptive analysis of baseline variables was followed by multivariate analysis (Cox proportional hazards models and generalized linear model) to compare the health and economic outcomes, including mortality, length of hospital stay(LoS),and hospital costs associated with a positiveNRS2002result. Results:The prevalence of a positiveNRS2002result was65.3%(n=3517).Prevalence of ‘at-risk’ patients(NRS2002 scores of 3+)was highest in patients with cardiac conditions (31.5%) and lowest in patients with diseases of the respiratory system(6.9%).Controlling for sex, age, education, type of insurance, smoking status, the main diagnosed disease and Charlson comorbidity index (CCI),the multivariate analysis showed that the NRS2002 score=3(hazard ratio [HR] 1.376,95% confidence interval [CI]1.031to1.836) were associated with approximately a 1.5-fold higher likelihood of death. NRS 2002 scores=4 (HR1.982,95%CI1.491to2.633) and NRSscores≥5(HR 1.982,95%CI1.498 to2.622) were associated with a two-fold higher likelihood of death, compared with NRS 2002 scores＜3.A NRS 2002 score of 3(percentage change 16.4, 95% CI 9.6 to 23.6), score of 4(32.4,95%CI24to41.4),and scores of ≥5 (36.8,95%CI 28.3to45.8)were associated with a significantly (16.4%,32.4%, and 36.8%, respectively) higher likelihood of increased LoS compared with aNRS2002scores＜3.The NRS2002score=3group(17.8, 95% CI 8.6 to 27.7)was associated with a17.8%,the NRS2002score=4group (31.1,95%CI 19.8 to43.5) a31.1%, and the NRS2002 score≥5group(44.3,95%CI32.3to57.4) a44.3%,higher likelihood of increased hospital costs compared with a NRS 2002scores＜3group.Specifically, the most notable mortality-specific comorbidity and LoS-specific comorbidity was injury, while the most notable cost-specific comorbidity was diseases of digestive system. Conclusions: This study demonstrated the high burden of undernutrition at the time of hospital admission on the health and hospital cost outcomes for older immobile inpatients. These findings underscore the need for nutritional risk screening in all Chinese hospitalized patients, and improved diagnosis, treatment, and nutritional support to improve immobile patient outcomes and to reduce healthcare costs.